2005
DOI: 10.1086/498219
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Low‐Intensity Polyparasite Helminth Infections in Anemia

Abstract: Low-intensity polyparasite infections were associated with increased odds of having anemia. In most parts of the developing world, concurrent infection with multiple parasite species is more common than single-species infections. This study suggests that concurrent low-intensity infections with multiple parasite species result in clinically significant morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 62 publications
3
112
1
1
Order By: Relevance
“…Anemia was not associated with significant intestinal parasites, in contrast to many studies. 27,28 However, it should be noted that parasites that cause anemia, especially helminthes, were less prevalent in this study.…”
Section: Discussionmentioning
confidence: 58%
“…Anemia was not associated with significant intestinal parasites, in contrast to many studies. 27,28 However, it should be noted that parasites that cause anemia, especially helminthes, were less prevalent in this study.…”
Section: Discussionmentioning
confidence: 58%
“…22 Higher prevalences of low-intensity helminth infections could also have far-reaching consequences on burden estimates because recent studies point to significant morbidity associated with even light infection intensities. 30 The encouraging results obtained with the FLOTAC method for diagnosis of common soil-transmitted helminths call for further development and sequential validation steps. An issue that warrants particular investigation is to elucidate reasons for the significant differences observed in mean hookworm and T. trichiura infection intensities when comparing FLOTAC with Kato-Katz.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although most studies have shown that the risk of anemia is much greater among children with moderate-to high-intensity hookworm infections, the presence of multiple low-intensity infections with helminths also increases the risk for anemia. 26 Given the very high prevalence of low-intensity helminth infections globally, praziquantel may further limit anemia-related morbidity by reducing the number of children coinfected with multiple helminths at low intensity.…”
Section: Discussionmentioning
confidence: 99%